Imam Ahmad’s Doctrine about Al-Hadith Al-Ḍa’īf (Weak Hadith) - Attorah, Abdul Aziz Husain (Journal of Islamic and Religious Studies, 2023)
This paper discusses the position of Imam Ahmad regarding Al-Ḥadīth Al-Da’īf (weak hadiths). According to the text, Imam Ahmad prioritized weak hadiths over analogy and personal opinions. The author mentions that some scholars argued that weak hadiths should only be used without stronger evidence or when there is no contradiction. However, Imam Ahmad reportedly used weak hadiths even without stronger evidence. Additionally, the author notes that some scholars suggest using weak hadiths in matters of virtues but not in legal rulings. The paper also quotes Ibn Taymiyyah, who explains that Imam Ahmad used weak hadiths in matters of virtue not to prove a particular action's desirability but to demonstrate its reward's greatness. Furthermore, it is mentioned as well that Imam Ahmad sometimes wrote down weak hadiths to consider them, especially if their narrators were not accused of being unreliable. The paper concludes that some scholars argue that other weak hadiths could strengthen weak hadiths if their narrators were not accused of being unreliable.